Osteomyelitis of maxilla: A rare finding from a radiologist point of view - Jayachandran Sadaksharam; Manikandan Murugesan (Wolters Kluwer Medknow Publications, 2019)
Osteomyelitis is an inflammatory process of both cortical and medullary bone. In the maxillofacial skeleton, it can be seen more commonly in mandible as compared to the maxilla. Here, we present a rare case of osteomyelitis involving the entire maxillae in a 55-year-old male patient highlighting the clinical findings and radiographic features with treatment modalities.